Пошаговое объяснение:
а)
[tex]y- \frac{7}{12}y = 4\frac{1}{6} \\y*(1-\frac{7}{12}) = 4\frac{1}{6} \\\frac{5}{12}y=\frac{25}{6} \\y= \frac{25}{6}:\frac{5}{12}\\ y= \frac{25*12}{6*5} \\y= 10[/tex]
б)
[tex]x-\frac{9}{16}x=5\frac{1}{4} \\x*(1-\frac{9}{16} )= 5\frac{1}{4} \\\frac{7}{16}x=\frac{21}{4} \\x= \frac{21}{4}:\frac{7}{16}\\ x= \frac{21*16}{4*7} \\x= 12[/tex]
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Пошаговое объяснение:
а)
[tex]y- \frac{7}{12}y = 4\frac{1}{6} \\y*(1-\frac{7}{12}) = 4\frac{1}{6} \\\frac{5}{12}y=\frac{25}{6} \\y= \frac{25}{6}:\frac{5}{12}\\ y= \frac{25*12}{6*5} \\y= 10[/tex]
б)
[tex]x-\frac{9}{16}x=5\frac{1}{4} \\x*(1-\frac{9}{16} )= 5\frac{1}{4} \\\frac{7}{16}x=\frac{21}{4} \\x= \frac{21}{4}:\frac{7}{16}\\ x= \frac{21*16}{4*7} \\x= 12[/tex]